Changing epidemiology of dengue in Sri Lanka-Challenges for the future. - Gathsaurie Neelika Malavige; Chandima Jeewandara; Azhar Ghouse; Gayasha Somathilake; Hasitha Tissera (Public Library of Science (PLoS), 2021)
Background Dengue infections are on the rise in Sri Lanka and are spreading to all areas in the country. Here, we discuss the changes in dengue epidemiology in Sri Lanka in relation to changes in age distribution, changes in seroprevalence rates over time, and possible reasons contributing to such changes. Methods and findings Although the incidence of dengue increased 20-fold from the year 2000 to 2012 and a further 3-fold from 2012 to 2019, this increase is not reflected in a similar increase in the age-stratified seropositivity rates for dengue. For instance, the annual seroconversion rates were 0.76% in 2013 and 0.91% in 2017. The annual seroconversion rates in the 6 to 17 age group were 1.5% per year in 2003, 3.9% in 2013, and 4.1% in 2017. In addition, although a 13-fold increase in dengue was seen in those who were <19 years of age, a 52.4-fold increase was seen in the 40- to 59-year age group. The case fatality rates (CFRs) have similarly changed, with 61.8% of deaths occurring in those <19 years of age in the year 2000, while in 2012 to 2018, the highest CFR were seen in those who were aged 20 to 39 years. Although there has been a marked increase in the number of cases, the vector densities did not change during a 4-year period. The proportion of adult individuals experiencing a secondary dengue infection has also remained between 65% and 75% between the years 2004 and 2018. Conclusions A change in the ratio of symptomatic to asymptomatic infections can give rise to changes in the reported incidence of dengue. In order to take an appropriate policy decision in dengue control activities, it would be important to study the changes in virus serotypes, vector dispersion, and densities. Further, the contribution of the rise in metabolic diseases to an increase in the symptomatic as well as more severe infections due to dengue is explored.